(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Because of the requirement for expanded force execution, supercapacitors are arising as an option in contrast to traditional electric energy stockpiling gadgets. In view of their one of a kind properties, carbon nanotubes are a promising material for cutting edge supercapacitors. In particular, the utilization of nanotubes to build supercapacitor cathodes can expands the force thickness and execution of supercapacitors comparative with regular dielectric capacitors. The creators clarify various techniques for developing supercapacitors utilizing nanostructure materials and furthermore diagram the advantages of this imaginative type of energy stockpiling.